Aktualisasi Pembelajaran Keagamaan melalui Kultum Khitobiyah Rohani Islam (Rohis) dalam Pengembangan Public Speaking dan Spiritualitas Peserta Didik SMAN 2 Tuban - Asma Hidayatul Hasanah; Fatimatuz Zahro; Izzatul Firdaus; Rr. Kusuma Dwi Nur Ma’rifati (Jurnal Budi Pekerti Agama Islam, 2026)
Religious learning in secondary schools is not only implemented through intracurricular activities but is also strengthened by applicative extracurricular programs. One form of actualizing religious learning is kultum khitobiyah activities within the Islamic Spiritual Organization (Rohani Islam/Rohis). This study aims to describe the actualization of religious learning through Rohis kultum khitobiyah activities in developing students’ public speaking skills and spirituality at SMA Negeri 2 Tuban. This research employed a qualitative approach using field research methods. Data were collected through observation, interviews, and documentation, while data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that kultum khitobiyah activities effectively actualize religious learning through students’ active involvement in religious preaching practices. These activities contribute positively to the development of public speaking skills, particularly in terms of courage, self-confidence, and the ability to deliver ideas systematically. Furthermore, kultum khitobiyah activities also play a significant role in strengthening students’ spirituality, as reflected in increased religious awareness, internalization of Islamic values, and the manifestation of religious attitudes in daily life. Therefore, kultum khitobiyah activities within the Rohis extracurricular program have a strategic role in reinforcing religious learning by integrating communication skill development with students’ spiritual formation.